Differential diagnosis of leg ulcers. (March 2013) - Pannier, F; Rabe, E
Leg and foot ulcers are symptoms of very different diseases. The aim of this paper is to demonstrate the differential diagnosis of leg ulcers. The majority of leg ulcers occur in the lower leg or foot. In non-venous ulcers the localization in the foot area is more frequent. The most frequent underlying disease is chronic venous disease. In 354 leg ulcers, Koerber found 75.25% venous leg ulcers, 3.66% arterial leg ulcers, 14.66% ulcers of mixed venous and arterial origin and 13.5% vasculitic ulcers. In the Swedish population of Skaraborg, Nelzen found a venous origin in 54% of the ulcer patients. Each leg ulcer needs a clinical and anamnestic evaluation. Duplex ultrasound is the basic diagnostic tool to exclude vascular anomalies especially chronic venous and arterial occlusive disease. Skin biopsies help to find a correct diagnosis in unclear or non-healing cases. In conclusion, chronic venous disease is the most frequent cause of leg ulcerations. Because 25% of the population have varicose veins or other chronic venous disease the coincidence of pathological venous findings and ulceration is very frequent even in non-venous ulcerations. Leg ulcers without the symptoms of chronic venous disease should be considered as non-venous.